After the great inventions: technological change in UK cotton spinning, 1780–1835. (28th May 2021) - Maw, Peter; Solar, Peter; Kane, Aidan; Lyons, John S.
Abstract: This article analyses the improvement of cotton‐spinning technologies in the years after the great inventions of Hargreaves, Arkwright, and Crompton. While these 'macro‐inventions' have attracted considerable historical attention, our understanding of the major changes in types and sizes of spinning machines used in the UK between the 1780s and the onset of state‐collected factory statistics in the 1830s is still largely based on the experience of high‐profile firms or specific technologies and regions. A new dataset of 1, 465 machinery advertisements published in newspapers in England, Scotland, and Ireland between 1780 and 1835 allows us to examine the temporal and spatial dimensions of the market for cotton‐spinning machinery, the timings of transitions between different spinning machines, and increases in machine size. The article demonstrates the importance of post‐invention technical improvements in the cotton industry, showing that the productivity increases associated with the initial transition from hand to machine spinning have been overstated and that larger gains were made in the 'micro‐invention' phase, when spinning machines became larger and faster, and required fewer workers to operate them.